2020
DOI: 10.21203/rs.2.20289/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the ”Extra-Corporeal Membrane Oxygenation Gap" in Veno-Arterial Configuration for Adult Patients: Timing and Causes of Death. Defining the Veno-Arterial Extracorporeal Membrane Oxygenation Gap

Abstract: Background Timing and causes of hospital mortality in adult patients undergoing veno-arterial extracorporeal membrane oxygenation (V-A ECMO) have been poorly described. Aim of the current review was to investigate the timing and causes of death of adult patients treated with V-A ECMO, and subsequently define the “V-A ECMO gap”, which represents the patients who are successfully weaned of ECMO but eventually die during hospital stay.Methods A systematic search was performed using electronic MEDLINE and EMBASE d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…As such, mortality and timing of mortality (either on‐ECMO or after weaning) of V‐V ECMO patients is still not fully elucidated. Although less well pronounced as in V‐A ECMO, 11 we still observe a relatively large group of patients that decease despite successful weaning from ECLS in V‐V ECMO patients. In a previously published review of V‐A ECMO patients by our research group, 11 this discrepancy was identified as the ECMO gap , which can also be applied to patients undergoing V‐V ECMO: the V‐V ECMO gap .…”
Section: Introductionmentioning
confidence: 64%
“…As such, mortality and timing of mortality (either on‐ECMO or after weaning) of V‐V ECMO patients is still not fully elucidated. Although less well pronounced as in V‐A ECMO, 11 we still observe a relatively large group of patients that decease despite successful weaning from ECLS in V‐V ECMO patients. In a previously published review of V‐A ECMO patients by our research group, 11 this discrepancy was identified as the ECMO gap , which can also be applied to patients undergoing V‐V ECMO: the V‐V ECMO gap .…”
Section: Introductionmentioning
confidence: 64%